On the origin of 300 K near-band-edge luminescence in CdTe - Glinchuk, K.D.; Litovchenko, N.M.; Strilchuk, O.N. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2003)
A careful analysis of 300 K near-band-edge luminescence from bulk CdTe and cadmium telluride films is made. It is shown that: (i) the observed difference in 300 K peak positions of the near-band-edge luminescence hvm in CdTe crystals and films, and (ii) the hvm shift to lower energies as the excitation intensity is increased, could not be satisfactory explained by an assumption that free excitons dominate in the formation of the above luminescence. So, the origin of 300 K near-band-edge luminescence in CdTe is not mainly the free exciton one as was proposed earlier, and needs further examination.